Pengaruh Strategi Active Learning Terhadap Minat Belajar Matematika Siswa Kelas V SDN Tayem 01 Karangpucung - Tyas Apriliana, Aisha; Febriyani, Shoimatun; Isnawati, Febri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Learning strategies have a considerable role in teaching and learning activities. The role of teachers in the learning process is very important, it is the teacher who designs learning methods, models, and strategies to achieve the expected learning goals, especially to attract the students' own interest in learning. This study aims to determine the influence of active learning strategies on mathematics learning interest. The research method used is a quantitative research method with a type of pre-experimental research. This research was carried out with a one-group pretest posttest design research design. Pretest and posttest are carried out by collecting data using questionnaires. Questionnaires and observation sheets were used in data collection. This research was carried out by providing active learning strategies to grade V students of SDN Tayem 01 Karangpucung in mathematics. The data obtained were analyzed using the t-test. The results of the study with the title The influence of active learning strategies on the interest in learning mathematics of Class V students of SDN Tayem 01 Karangpucung had a significant effect on an increase when learning using the active learning strategy.